2021
DOI: 10.3389/fmicb.2021.685698
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Device-Integrated Drug Delivery System for Local Inhibition of Urinary Tract Infection

Abstract: Background: Catheter-associated urinary tract infection (CAUTI) is a frequent community-acquired infection and the most common nosocomial infection. Here, we developed a novel antimicrobial catheter concept that utilizes a silicone-based interpenetrating polymer network (IPN) as balloon material to facilitate a topical slow-release prophylaxis of antibacterial agents across the balloon to the urinary bladder.Methods: The balloon material was achieved by modifying low shore hardness silicone tubes with a hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 59 publications
(78 reference statements)
1
22
0
Order By: Relevance
“…However, they are not sufficient to avoid the insurgence of these infections, and therefore, several new strategies have been reported. Among them, coatings with antibacterial properties have been proposed to limit the colonization and proliferation of infectious bacteria and the subsequent biofilm formation ( Li et al, 2021 ; Stærk et al, 2021 ). Specifically, drug-eluting or controlled drug release coatings gained interest from researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are not sufficient to avoid the insurgence of these infections, and therefore, several new strategies have been reported. Among them, coatings with antibacterial properties have been proposed to limit the colonization and proliferation of infectious bacteria and the subsequent biofilm formation ( Li et al, 2021 ; Stærk et al, 2021 ). Specifically, drug-eluting or controlled drug release coatings gained interest from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The development of coatings capable of releasing antibacterial compounds at the infection site for a sustained period represents an interesting approach to address the issue. The local delivery of antibacterial agents offers the advantage of a higher concentration at the wound site as compared to systemic delivery, avoiding harmful secondary effects ( Stærk et al, 2021 ). Moreover, the possibility to modulate over time the presence of effective and sustainable concentrations of the antibacterial agents at the site of interest is highly promising ( Viola et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some strategies to control UD biofilms include antimicrobial lubricants, bladder instillation or irrigation, antimicrobial agents in collection bags, and the administration of antibiotics [ 13 ]. Recently, in a novel approach, the balloon on Foley catheters was transformed into a permeable membrane allowing localized and continuous delivery of antibiotics to the bladder and was shown to eradicate a provoked uropathogenic E. coli infection [ 23 ]. Moreover, the development of new surfaces that inhibit biofilm formation through antimicrobial agent’s release, contact-killing, inhibition of microbial adhesion, and the disruption of biofilm architecture have been suggested to reduce the incidence of device-associated UTIs [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domesticated pigs are, by contrast, naturally susceptible to UTI, like humans, and share important features of human UTI with respect to inflammatory response, physiology, urinary tract anatomy and urine composition [5–8]. Recently we showed that this animal is highly susceptible to E.…”
Section: Full-textmentioning
confidence: 99%
“…Therefore, this animal does not reflect the natural susceptibility to UTI that is seen in human patients. Domesticated pigs are, by contrast, naturally susceptible to UTI, like humans, and share important features of human UTI with respect to inflammatory response, physiology, urinary tract anatomy and urine composition [5][6][7][8]. Recently we showed that this animal is highly susceptible to E. coli UTI and becomes consistently infected at an inoculum of 10 2 colony-forming units (c.f.u.)…”
mentioning
confidence: 99%